Chronic invasive fungal sinusitis: one case report - Sousa e Castro, Sandra (2009)
Sinusitis is a common disorder affecting approximately 20% of the population. Whether fungi can exist in sinus mucus without causing disease is unclear. Once considered uncommon, fungal sinusitis has increased dramatically over the past two decades. The exact prevalence rate is, however, not known.ln the most recent classification system, fungal sinusitis is divided into noninvasive and invasive forms. Noninvasive fungal sinusitis has been categorized into fungus ball and allergic fungal sinusitis. lnvasive fungal sinusitis has been divided into acute fulminant fungal sinusitis, chronic invasive fungal sinusitis and granulomatous invasive fungal sinusitis. The development of these forms depends on the immunologic relationship of the fungus to the host, as invasive form usually occurs in immunocompromised hosts.The authors present a case of a 62-years-old woman, immunocompetent, with headache and blindness. lmaging studies showed sphenoidal sinus opacified with bone erosion. During surgery a yellow-greenish mass was detected on the sphenoidal sinus. Microbiologic examination revealed the presence of Aspergillus fumigatus. lt was prescribed variconazol and one week after surgery she had no complaints. Ten months after surgery she stays asymptomatic.